Parental Control Model for High School E-Learning - Sri Suning Kusumawardani; Ridi Ferdiana (Forum Teknik, 2013)
Adopting e-Learning in high school is challenging. The main problem in this situation is the adoption of e-Learning as a self-paced learning. In universities, the problem rarely happens since the students in universities have an awareness to explore and to learn by themselves. In high school level, student awareness is limited.High school students more likely need a control mechanism to use e-Learning. In this research, an efort is made to create a model that collaborate parents to control e-Learning usages. The collaboration of parents in e-Learning strongly believed can provides additional value of effectiveness in student e-Learning usage.The result of this research is a model called PCM (Parental Control Model). PCM is an architectural model that contains of information and software architecture that will cover business process collaboration between parent and student.Keywords: e-Learning, parental control model, software architecture, interaction model